2016
DOI: 10.1002/jsfa.8018
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inhibition of μ‐calpain on the myofibril structure and myofibrillar protein degradation in postmortem ovine muscle

Abstract: Comparatively, myosin heavy chain and actin were found to be less sensitive to μ-calpain compared to desmin, troponin T and troponin I. These findings provide a better understanding of the contribution of μ-calpain to the myofibril structure and myofibrillar protein degradation of ovine muscle. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 34 publications
0
9
0
1
Order By: Relevance
“…The color stability of meat with normal energy metabolism rate is good and the abnormal energy metabolism rate leads to development of PSE, DFD, and other defected meat (Hopkins et al., 2015; Ijaz et al., 2020). Changes in the structure and function of skeletal and myofibrillar proteins in lamb with abnormal energy metabolism result in dry or softened meat (Li, Li, Gao, Du, & Zhang, 2017). In the lamb with fast energy metabolism rate, the pH decline rate was increased, which led to the degeneration of muscle fiber structural proteins and the increase of fluid losses (Wang, He, et al., 2016).…”
Section: Protein Phosphorylationmentioning
confidence: 99%
“…The color stability of meat with normal energy metabolism rate is good and the abnormal energy metabolism rate leads to development of PSE, DFD, and other defected meat (Hopkins et al., 2015; Ijaz et al., 2020). Changes in the structure and function of skeletal and myofibrillar proteins in lamb with abnormal energy metabolism result in dry or softened meat (Li, Li, Gao, Du, & Zhang, 2017). In the lamb with fast energy metabolism rate, the pH decline rate was increased, which led to the degeneration of muscle fiber structural proteins and the increase of fluid losses (Wang, He, et al., 2016).…”
Section: Protein Phosphorylationmentioning
confidence: 99%
“…К ним относятся белки теплового шока или шапероны и ферменты, участвующие в метаболизме [27]. Существует также сильная корреляция нежности с белками, которые защищают от окисления [28], и известно, что кальпаин очень восприимчив к окислению [29]. На активность протеаз также может влиять посттрансляционная модификация.…”
Section: кальпаиныunclassified
“…Troponin-T is located near actin and important for regulating actin-myosin interaction and maintaining the strength of thin filament (Yang et al, 2019). It is reported that troponin-T is cleaved by calpains (m/mcalpain), present in the sarcoplasm, and also by the lysosomal protease cathepsin B and L (de Oliveira et al, 2019;Li et al, 2017). Calpains are active at early stages, while the action of cathepsin B is related to the degree of postmortem lysosomal membrane breakdown, which occurs due to permeabilisation of the lysosomal membrane related to depletion of ATP reserves and malfunctioning of ionic pumps (Campus et al, 2010).…”
Section: Protein Denaturation and Degradationmentioning
confidence: 99%